The Role of Point-of-Care C-Reactive Protein Testing in Antibiotic Prescribing for Respiratory Tract Infections: A Survey among Swiss General Practitioners - Nahara Anani Martínez-González; Andreas Plate; Levy Jäger; Oliver Senn; Stefan Neuner-Jehle (MDPI AG, 2022)
Understanding the decision-making strategies of general practitioners (GPs) could help reduce suboptimal antibiotic prescribing. Respiratory tract infections (RTIs) are the most common reason for inappropriate antibiotic prescribing in primary care, a key driver of antibiotic resistance (ABR). We conducted a nationwide prospective web-based survey to explore: (1) The role of C-reactive protein (CRP) point-of-care testing (POCT) on antibiotic prescribing decision-making for RTIs using case vignettes; and (2) the knowledge, attitudes and barriers/facilitators of antibiotic prescribing using deductive analysis. Most GPs (92-98%) selected CRP-POCT alone or combined with other diagnostics. GPs would use lower CRP cut-offs to guide prescribing for (more) severe RTIs than for uncomplicated RTIs. Intermediate CRP ranges were significantly wider for uncomplicated than for (more) severe RTIs (p = 0.001). Amoxicillin/clavulanic acid was the most frequently recommended antibiotic across all RTI case scenarios (65-87%). Faced with intermediate CRP results, GPs preferred 3-5-day follow-up to delayed prescribing or other clinical approaches. Patient pressure, diagnostic uncertainty, fear of complications and lack of ABR understanding were the most GP-reported barriers to appropriate antibiotic prescribing. Stewardship interventions considering CRP-POCT and the barriers and facilitators to appropriate prescribing could guide antibiotic prescribing decisions at the point of care.